The Evolution of Political Party in Indonesia: PSI Towards a Digital Party - Alvin, Silvanus (Jurnal Komunikasi, 2022)
Internet penetration and technological developments have transformed society into a digital community. Political communication cannot run stagnant but continues to advance following developments. In Europe, this digitalization phenomenon gave birth to a new form in the political field, namely the birth of digital parties. The term digital party cannot be applied to political parties that use social media as a means of communication, but rather a party that upholds and applies digital philosophy in its internal and external communication. Paolo Gerbaudo sparked the idea of ​​a Digital Party with five main criteria: cloud-based parties, participationism, hyperleader, superbase and plebiscitarianism 2.0. The main goal of digital parties is to empower people in an idealistic democratic sphere. In Indonesia, Partai Solidaritas Indonesia (PSI) is well-known as a political party filled with youngsters and uses digital apps for political communication. After the 2019 General Election ended and failed to enter the central parliament (DPR RI), PSI presented a digital platform called the Solidarity Application for the public. The Solidarity Apps is expected to bring PSI's elected district legislative members (DPRD) closer to the public. PSI is the first political party to present this digital medium to the public. This qualitative case study research examines three things academically: Firstly, why does PSI use the Solidarity Application as a form of political communication? Secondly, knowing the use of the Solidarity Application. Lastly, understanding PSI's position within the framework of the Digital Party concept of Paulo Gerbaudo. The researcher conducted in-depth interviews with Director of Digital Platform of PSI, Sigit Widodo and a Member of the District Legislative from PSI, Yoel Yosaphat. This paper argues that PSI cannot yet be categorized as a digital party. Nonetheless, PSI is already in the right direction to evolve as a digital party in Indonesia because evolution is a process that takes time. Several obstacles in the pursuit of a digital party are discussed.